Peran Dukungan Sosial Keluarga dalam Proses Penerimaan Diri pada Remaja Korban Kekerasan Seksual - Amalia, Fiqih; Darojat, A’yunin Akrimni (Al Huwiyah: Journal of Woman and Children Studies, 2022)
Throughout 2022 cases of sexual violence against minors that occurred in Indonesia were reported as many as 16,444 cases and still growing (https://kekerasan.kemenpppa.go.id/ringkasan). Sexual violence is a crime that is very heinous, immoral, despicable, and violates norms where the victims are women, both adults and minors. Sexual violence against children has an emotional and physical impact on the victim. Emotionally, children as victims of sexual violence experience stress, depression, mental shock, feelings of guilt and self-blame, fear of relating to others, nightmares, and insomnia. This prompted researchers to conduct research related to the role of family social support on self-acceptance in adolescent victims of sexual violence, with the aim of obtaining an overview of the forms of social support provided by families in the process of self-acceptance to adolescent victims of sexual abuse. This research was conducted using a qualitative method with a case study approach. As for the data collection, researchers used structured interviews through instruments that have been provided by researchers with the aim of knowing the form of support provided by the family. With data sources, namely 3 teenage victims of sexual harassment, 1 mother of a teenage victim of sexual harassment, grandparents of one of the victims of sexual harassment and a cousin of one of the victims of sexual harassment.